Impact of Precipitate Characteristics and Precipitation Conditions on the Settling Performance of a Sulfide Precipitation Process: An Exhaustive Characterization of the Aggregation Behavior - Romero-Figueroa, J (Elsevier B.V., 2019)
The sulfide precipitation process is currently the most successful technology for recovering cyanide and copper in cyanidation gold plants. The application of this chemical process has been implemented in the SART (Sulfidization, Acidification, Recycling, and Thickening) process. This process includes thickening and filtering unit operations to separate the solids precipitated in the sulfidization reactor. Nevertheless, solid-liquid separation in the thickener has not been optimized, resulting in the loss of copper precipitates in the overflow and, consequently, inducing a reduction in copper recovery in the overall process. This performance could be influenced by the colloidal characteristics of the particles formed in the reaction, but only a few studies have found quantifiable evidence in this regard. Moreover, the impact of the main variables of the process (e.g., pH, sulfide content, and reaction time) on the aggregation behavior has not been studied. Thus, this work attempts to reduce the current lack of scientific understanding of the SART process with respect to the industrial practice. In this context, the goal of this work was to carry out a chemical characterization, particle electrical charge (zeta potential) assessment, chemical computational simulation and settling tests of precipitates obtained from sulfide precipitation assays, in order to create a deep characterization of copper and zinc precipitates. The main results attend to understand the aggregation behavior of the precipitates, the relevance of reaction parameters (pH and sulfide addition) in the aggregation characteristics and its impact in settling results. This study is the first research focused on the characterization of sulfide metal precipitates in cyanide media and its impact in the process. © 2019 Elsevier B.V.